Entendiendo el fenómeno Be (2017)
The following is a bibliographical review of Be stars and the so-called Be phenomenon both in the optical and in the infrarred, since 1867 in which the first observation of the spectrum of a Be star was reported. In these 150 years of understanding and theoretical comprehension it has been determined the following characteristics of the Be stars: They show emission lines of the Balmer series. They present a rotation velocity near to the critical velocity. Along with other mechanisms like non-radial pulsations, stellar winds, magnetism, the ejection of matter trough the equator occurs. Details about the ejection of matter as well as the size of the disc are still under investigation. Be stars present spectroscopic and photometric variability, called the Be phenomenon, which evidences the dynamics of the disk. The infrared studies also diagnose the characteristics of the disc such as optical depth, density, evolutionary state: stable, dissipating, building-up. We also obtained a catalog of stars that are observable in the San Pedro Mártir Observatory, Múxico, in which it is indicated if the variation of the H alpha line is stable, intense, or if it appears in absorption. It was found that 18 of the 39 stars show intense variations of the H alpha line over a time span of 18 years, 18 stars present slight variations of the H alpha line, and 3 stars show the H alpha in absorption indicating that their discs are almost dissipated.--Tomado del Formato de Documento de Grado.